Spending to save? State health expenditure and infant mortality in India - Sonia Bhalotra (Institute for the Study of Labor (IZA), 2007)
There are severe inequalities in health in the world, poor health being concentrated amongst poor people in poor countries. Poor countries spend a much smaller share of national income on health expenditure than do richer countries. What potential lies in political or growth processes that raise this share? This depends upon how effective government health spending in developing countries is. Existing research presents little evidence of an impact on childhood mortality. Using specifications similar to those in the existing literature, this paper finds a similar result for India, which is that state health spending saves no lives. However, upon allowing lagged effects, controlling in a flexible way for trended unobservables and restricting the sample to rural households, a significant effect of health expenditure on infant mortality emerges, the long run elasticity being about -0.24. There are striking differences in the impact by social group. Slicing the data by gender, birth-order, religion, maternal and paternal education and maternal age at birth, I find the weakest effects in the most vulnerable groups (with the exception of a large effect for scheduled tribes).
Keywords: 300; Gesundheitskosten; Kindersterblichkeit; Indien